A first record of Fissimentum Cranston & Nolte (Diptera: Chironomidae) in Peninsular Malaysia - Ahmad A.K.; Siti Hafizah A. (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2017)
A new record of Fissimentum Cranston & Nolte (Diptera: Chironomidae), Fissimentum sp by its immature stage has been recorded from upstream of Tampik River Pahang, Malaysia for the first time and been described at larval stage. This genus is distinguished from others by having a mentum with a distinct cleft mid, with 6 segmented antenna, in combination with louterborn organs at the apex of segment 2 or 3. Mandible remarks with large seta subdentalis and lacking of pecten mandibularis and seta interna. Descriptions, diagnosis and line drawings of larva material are provided. A brief note on the ecology of the genus is also given.